Sustained Effectiveness of Evidence-Based Parenting Programs After the Research Trial Ends - Gray, Gemma R.; Totsika, Vasiliki; Lindsay, Geoff (Frontiers in Psychology, 2018)
Despite ample evidence of the efficacy and effectiveness of evidence-based parenting programmes (EBPPs) within research-led environments, there is very little evidence of maintenance of effectiveness when programmes are delivered as part of regular service provision. The present study examined the effectiveness of EBPPs provided during a period of sustained service-led implementation in comparison to research-led effectiveness evaluation. Data from 3706 parents who received EBPPs during sustained implementation by services were compared to data from 1390 parents who had participated in an earlier researcher-led effectiveness trial of a national roll-out of EBPPs in England. In both phases, parents completed measures of child behaviour problems, parenting style and parental mental well-being prior to starting parenting programmes (pre-test), at the end of the programmes (post) and at 12-months follow up. Results from Generalised Estimating Equations controlling for potential covariates indicated significant improvements in child behaviour problems during sustained implementation, similar to the effectiveness phase; significant improvements in parenting style which were larger than the effectiveness phase at 12-month follow up; and significant improvements in parental mental well- being. Our findings demonstrate effective maintenance of gains when EBPPs are provided as part of regular provision across a large sample of English parents. Successful long-term implementation should consider effectiveness of EBPPs across the population, given the large contextual changes that take place between researcher-led evaluations and service take-up. Our findings support the integration of EBPPs in public health approaches to addressing child behaviour problems and parent well-being.